Expansion of the Inguinal Adipose Tissue Depot Correlates With Systemic Insulin Resistance in C57BL/6J Mice - Fryklund, Claes; Neuhaus, Mathis; Morén, Björn; Borreguero-Muñoz, Andrea; Lundmark, Richard; Stenkula, Karin G. (Frontiers in Cell and Developmental Biology, 2022)
To accommodate surplus energy, the adipose tissue expands by increasing adipocyte size (hypertrophy) and number (hyperplasia). The presence of hypertrophic adipocytes is a key characteristic of adipose tissue dysfunction. High-fat diet (HFD) fed C57BL/6J mice are a commonly used model to study obesity and obesity-related complications. In the present study, we have characterized adipose plasticity, at both the cellular and tissue level, by examining the temporal development of systemic insulin resistance and adiposity in response to HFD-feeding for 4, 8, and 12 weeks (4w, 8w, and 12w). Within the same time frame, we examined systemic metabolic flexibility and adipose plasticity when switching from HFD- to chow-diet during the last 2 weeks of diet intervention (referred to as the reverse (REV) group: 4wREV (2w HFD+2w chow), 8wREV (6w HFD+2w chow), 12wREV (10w HFD+2w chow)). In response to HFD-feeding over time, the 12w group had impaired systemic insulin sensitivity compared to both the 4w and 8w groups, accompanied by an increase in hypertrophic inguinal adipocytes and liver triglycerides. After reversing from HFD- to chow-feeding, most parameters were completely restored to chow control levels for 4wREV and 8wREV groups. In contrast, the 12wREV group had a significantly increased number of hypertrophic adipocytes, liver triglycerides accumulation, and impaired systemic insulin sensitivity compared to chow-fed mice. Further, image analysis at the single-cell level revealed a cell-size dependent organization of actin filaments for all feeding conditions. Indeed, the impaired adipocyte size plasticity in the 12wREV group was accompanied by increased actin filamentation and reduced insulin-stimulated glucose uptake compared with chow-fed mice. In summary, these results demonstrate that the C57BL/6J HFD-feeding model has a large capacity to restore adipocyte cell size and systemic insulin sensitivity, and that a metabolic tipping point occurs between 8 and 12w of HFD-feeding where this plasticity deteriorates. We believe these findings provide substantial understanding of C57BL/6J mice as an obesity model, and that an increased pool of hypertrophic ING adipocytes could contribute to aggravated insulin resistance.